Riparian forest buffers on agricultural lands in the Oregon coast range : Beaver Creek riparian project as a case study - Bishaw, Badege; Emmingham, William H.; Rogers, William Reinhold; Oregon State University. Forest Research Laboratory
Riparian areas in the Pacific Northwest have traditionally been a source of natural resources, such as timber and grazing, and have been used as transportation corridors and homestead sites. A primary impact of use has been the removal of riparian trees, the crowns and roots of which provide shade and stream bank protection. Increases in water temperature can be lethal to salmonid fish, and decreasing salmon populations over the past few decades have resulted in an urgent need for improving the management of watersheds, fish habitat, and water quality. Leaving stream-side buffers is now required by state forest practices regulations on forest lands, but no regulations are in place on agricultural lands, where riparian trees have frequently been removed. In 1995, the Beaver Creek Riparian Buffer Project was established to develop better information about how to establish riparian buffers on coastal pastureland near Newport, Oregon. No riparian trees were present when the trial was begun. A replicated tree filter belt trial was established along the south bank of the creek to compare unplanted pasture (controls) with commercially valued red alder (Alnus rubra) planted at 6-ft spacing in belts 1 row, 3 rows, and 6 rows wide. Tree survival and height and diameter growth were compared, as well as the amount of shade produced by the three treatments and control. We used a LI-COR LAI-2000 Plant Canopy Analyzer to quantify shade. We found that intensive site preparation, continued vegetation management, and both fencing and tubing of tree seedlings were necessary to gain survival and protect seedlings from small rodents, beaver, and cattle. Fencing out cattle provided stream bank protection within 1 yr. Significant shading of the stream occurred 2–6 yr after planting, as trees grew tall enough to intercept a significant amount of light. Single row plantings that take a minimal amount of pasture offer significant shading only after 4–7 yr. A wider 6-row filter belt occupies a greater amount of pasture, but provides ...